2003
DOI: 10.1002/yea.981
|View full text |Cite
|
Sign up to set email alerts
|

Moderately lipophilic carboxylate compounds are the selective inducers of the Saccharomyces cerevisiae Pdr12p ATP‐binding cassette transporter

Abstract: Saccharomyces cerevisiae displays very strong induction of a single ATP-binding cassette (ABC) transporter, Pdr12p, when stressed with certain weak organic acids. This is a plasma membrane pump catalysing active efflux of the organic acid anion from the cell. Pdr12p action probably allows S. cerevisiae to maintain lower intracellular levels of several weak organic acid preservatives than would be expected on the basis of the free equilibration of the acid across the cell membrane. This in turn facilitates grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
1
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 37 publications
9
82
1
2
Order By: Relevance
“…7B). Earlier Hatzixanthis et al 39 demonstrated that H 2 O 2 did not affect PDR12 expression. Piper 2 also suggested that PDR12 induction by WOAs was not a direct response to oxidative stress in sorbate-exposed yeast cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…7B). Earlier Hatzixanthis et al 39 demonstrated that H 2 O 2 did not affect PDR12 expression. Piper 2 also suggested that PDR12 induction by WOAs was not a direct response to oxidative stress in sorbate-exposed yeast cells.…”
Section: Discussionmentioning
confidence: 88%
“…16,37,38 Yeast can extrude acid anions through the anion efflux pump Pdr12p, which has been found to mediate resistance to both AA and PA. 18 However, later works by the same research group reported that acetate did not induce expression of PDR12 gene, while PA did. 17,39 It was believed that expression of Pdr12p is controlled by the sole War1p transcriptional factor. 17 To date, it is well documented that weak acid stress-induced response depends on the following transcription factors: War1p, Msn2/Msn4p, Rim101p, and Haa1p, 5,38 and the sole War1p-target gene, PDR12, was identified among the genes activated by Haa1p in response to AA.…”
Section: Discussionmentioning
confidence: 99%
“…Resistances are induced to Acetic, but not propionic, sorbic or benzoic acids [19] Propionic, sorbic, benzoic acids, but not acetic acid [1,7] Key induced signalling pathway and activity HOG pathway signalling, leading to Hog1p MAP kinase activation [19] No evidence for a signalling pathway involvement; acid anion may act directly on the War1p transcription factor [13] Key action/target of the induced activity needed for the acquisition of resistance Phosphorylation of Fps1p, leading to Fps1p endocytosis [20] PDR12 gene induction, leading to an elevated plasma membrane level and activity of the Pdr12p ABC transporter [23,28] Probable related stress response Hog1p-directed downregulation of metalloid entry through the Fps1p channel [40] War1p activation in media containing leucine, methionine or phenylalanine as sole nitrogen source [9] Normal physiological function of the major target of the response Fps1p is the major glycerol channel of the plasma membrane, important for osmoadaptation [10,22,38] Pdr12p is also involved in export of the potentially toxic aromatic and branched-chain organic acids produced during amino acid catabolism [9] (2), a MAP kinase constitutively bound to, and that directly phosphorylates, Fps1p (3). This phosphorylation provides the signal for Fps1p endocytosis and degradation, eliminating this source of the acetic acid entry to the cell.…”
Section: Response To Inhibitory Acetic Acid Inhibitory Propionic Sormentioning
confidence: 99%
“…Acquisition of resistance to these larger acids appears to involve, not the loss of a membrane pore, but the induction of an activity catalysing active efflux of the acid anion from the cell (Figure 2b). Inhibitory amounts of propionic, sorbic and benzoic acid induce the activity of a zinc-finger transcription factor, War1p [7,13,28] (Table 1). Only a small number of genes are subject to War1p regulation and, of these, it seems that just a single gene -that encoding the Pdr12p plasma membrane ATP binding cassette (ABC) transporter -is of any major importance for weak organic acid resistance.…”
Section: Hog1p Map Kinase Directs a Different Stress Response When Acmentioning
confidence: 99%
See 1 more Smart Citation